High Oxygenation During Normothermic Regional Perfusion After Circulatory Death Is Beneficial on Donor Cardiac Function in a Porcine Model. Issue 7 (11th May 2022) - Moeslund, Niels; Long Zhang, Zhang; Bo Ilkjaer, Lars; Ryhammer, Pia; Cramer, Christine; Palmfeldt, Johan; Pedersen, Michael; Erasmus, Michiel Elardus; Tsui, Steven; Eiskjaer, Hans
Abstract : Background: Thoracoabdominal normothermic regional perfusion (NRP) is a new method for in situ reperfusion and reanimation of potential donor organs in donation after circulatory death by reperfusion of the thoracic and abdominal organs with oxygenated blood. We investigated effects of high oxygenation (HOX) versus low oxygenation (LOX) during NRP on donor heart function in a porcine model. Methods: Pigs (80 kg) underwent a 15-min anoxic cardiac arrest followed by cardiac reanimation on NRP using a heart-lung bypass machine with subsequent assessment 180 min post-NRP. The animals were randomized to HOX (FiO2 1.0) or LOX (FiO2 0.21 increased to 0.40 during NRP). Hemodynamic data were obtained by invasive blood pressure and biventricular pressure-volume measurements. Blood gases, biomarkers of inflammation, and oxidative stress were measured. Results: Eight of 9 animals in the HOX group and 7 of 10 in the LOX group were successfully weaned from NRP. Right ventricular end-systole elastance was significantly improved in the HOX group compared with the LOX group, whereas left ventricular end-systole elastance was preserved at baseline levels. Post-NRP cardiac output, mean arterial, central venous, and pulmonary capillary wedge pressure were all comparable to baseline. Creatinine kinase-MB increased more in the LOX group than the HOX group, whereas proinflammatory cytokines increased more in the HOX group than the LOX group. No difference was found in oxidative stress between groups. Conclusions: All hearts weaned from NRP showed acceptable hemodynamic function for transplantation. Hearts exposed to LOX showed more myocardial damage and showed poorer contractile performance than hearts reperfused with high oxygen. Abstract :